Successful treatment with sintilimab for SMARCA4-deficient non-small cell lung carcinoma: two case reports - Liwen Wang; Hua Ke; Chengdi Wang; Ke Wang (Discover Oncology)
Abstract SMARCA4, one of the subunits of the switch/sucrose nonfermentable (SWI/SNF) chromatin-remodeling complex, plays a pivotal role in transcriptional regulation. By disrupting histone-DNA contacts, this complex modulates gene expression patterns, and accumulating evidence suggests its tumor suppressor function. Inactivating mutations and loss of SMARCA4 expression have been shown in various tumors, with approximately 8% of non-small cell lung carcinomas (NSCLCs) harboring such alternations. SMARCA4-deficient NSCLC (SMARCA4-dNSCLC) represents a particularly aggressive subtype associated with dismal clinical outcomes. The reported overall survival (OS) for patients with SMARCA4-dNSCLC is only 2–3 months. In addition, chemotherapy has shown limited efficacy against this subtype and an effective treatment for SMARCA4-dNSCLC has not yet been established. Although immune checkpoint inhibitors (ICIs) have revolutionized the treatment landscape of advanced NSCLC, little is known about their efficacy in SMARCA4-dNSCLC. In this report, we present two cases of SMARCA4-dNSCLC patients who achieved remarkable clinical benefits following ICI treatment, with prolonged progression-free survival (PFS). These findings suggest that ICI-based immunotherapy combined with chemotherapy might be a promising therapy for SMARCA4-dNSCLC and may warrant early implementation following diagnosis to potentially prolong patient survival.